Coronary haemodynamic effects of nifedipine. Comparison with glyceryl trinitrate. Issue 5 (May 1983) - Stone, D L; Stephens, J D; Banim, S O
Abstract : The coronary haemodynamic effects of nifedipine and glyceryl trinitrate were compared in 22 patients undergoing investigations for suspected coronary artery disease. Myocardial blood flow was estimated by the coronary sinus thermodilution technique. In sinus rhythm nifedipine increased mean coronary sinus flow from 135 ml/min to 152 ml/min, and reduced arterio-coronary sinus oxygen difference from 12.4 to 10.96 ml/100 ml without causing a significant change in coronary vascular resistance or in myocardial oxygen consumption. Glyceryl trinitrate reduced mean coronary sinus flow from 165 to 111 ml/min, myocardial oxygen consumption from 19.2 to 11.9 ml/min, and arterio-coronary sinus oxygen difference from 11.7 to 10.9 ml/100 ml. There was a rise in coronary vascular resistance from 54 355 to 74 364 dynes s cm-5. During atrial pacing nifedipine reduced the arterio-coronary sinus oxygen difference from 11.99 to 11.0 ml/100 ml but had no significant effect on the other variables measured. Glyceryl trinitrate caused a fall in mean coronary sinus flow from 207 ml/min to 168 ml/min; myocardial oxygen consumption fell from 24 ml/min to 18 ml/min, while coronary vascular resistance rose from 41 714 to 51 234 dynes s cm-5. Direct comparison of the two drugs showed a significant difference in effects on coronary sinus flow and coronary vascular resistance in sinus rhythm. Both drugs appeared effective in relieving ischaemia as judged by a reduction of the incidence of pacing induced angina and an improvement in lactate status.